Not Too Tired to be Proactive: Daily Empowering Leadership Spurs Next-morning Employee Proactivity as Moderated by Nightly Sleep Quality - Schilpzand, Pauline; Houston, Lawrence; Cho, Jeewon (Academy of Management Journal, 2018)
Building on the Model of Proactive Motivation, we hypothesize that a leader’s daily empowering leadership behaviors function as a motivator for employees to display a greater amount of proactive goal-striving behavior, by means of enhanced daily proactive goal setting. Expanding the Model of Proactive Motivation, we incorporate the largely neglected self-regulatory resource perspective and hypothesize that employee sleep quality operates as a qualifying influence on employees’ ability to set and strive for proactive goals that allow employees to take advantage of empowerment opportunities. Using a time-lagged experience sampling methodology, our hypotheses were tested in a sample of 98 professionals who completed twice-daily surveys over a two-week period. Study results confirm our hypotheses that experiencing daily empowering leadership enhances employees’ next morning proactive behaviors of risk-taking and voice behavior due to more proactive goal setting at the start of the workday. Finally, employee next-day goal-setting and goal-striving behavior is especially enhanced for those employees who experienced higher levels of sleep quality. Theoretical and practical implications derived from our research are discussed.